Stress Management Skills in Post Earthquake Learning Through The Tutoring Modul for Student - Nusuki; Muhammad Ripli (Simposium Antar Bangsa Seminar dan Workshop)
The study was based on what happened in junior high school 2 selong, where stress in student moderate. Does administration tutoring module is useful for dealing with stress in learning in junior high school 2 Selong student in the academic year 2018/2019. Models of research in the development of pre-experimental, pre-experimental pra-experiment also called for a cursory models such as experimental but not experimental. This models is called the model experimentis weak because there is no equalization characteristics (Random) and no control variables. Tife used is one group pre test – postest desaign. Subjects in this study consisted of thirty student of class IX. While data analysis techniques used are the t-test formula polled variants. From the results of the questionnaire dealing with stress in the study were used as the experimental class after being given a pre-test is still medium category with a total score is 2322 with an everage value of 77,4. Specifically it appears that the number of children being categorized as many as 27 people (90%) and there is the third highest score 3 people (10%). While the results of the analysis of the questionnaire dealing with stress in learning in class IX students at junior high school 2 Selong were used as the experimental class after being given a pos-test in the form of activities gudance through guidance modules to learn that the thirty students who are subjected to low category, abtained a total score as many as 1926 with an average value of 64,2 with the lowest score is 12 people (40%). Seen from a comparison score pre-test and post-test decrease is 77,4<64,2 it is said successful research. By showing t-count>t-tabel (2,439>2,002). It can be concluded that by providing affective guidance modules learn to cope with stress learning in class IX students at junior high schools 2 Selong the academic year 2018/2019.